2017
DOI: 10.1016/j.colsurfa.2017.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Water in oil emulsions from hydrophobized metal membranes and characterization of dynamic interfacial tension in membrane emulsification

Abstract: Hydrophobization of metal surfaces is reported based on silanization reactions. The aim was its application to metal porous membranes for the production of water in oil emulsions using a process known as membrane emulsification. A vertical oscillating membrane system was used to carry out drop formation experiments. It is shown that drop size can be tuned between 35 and 85 µm by changing just the surfactant concentration in the continuous phase. In addition, a method to determine the percentage of active pores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Equation requires knowledge of the number of pores participating in the membrane emulsification process. It is well‐known that this is rarely the same number as the total number of pores present, as preferential flow through some pores occurs . For the validation work based on Equation , the number of active pores was modeled at 50 and 60%, values that appear reasonable based on recent work reported with this membrane type .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation requires knowledge of the number of pores participating in the membrane emulsification process. It is well‐known that this is rarely the same number as the total number of pores present, as preferential flow through some pores occurs . For the validation work based on Equation , the number of active pores was modeled at 50 and 60%, values that appear reasonable based on recent work reported with this membrane type .…”
Section: Resultsmentioning
confidence: 99%
“…It is well‐known that this is rarely the same number as the total number of pores present, as preferential flow through some pores occurs . For the validation work based on Equation , the number of active pores was modeled at 50 and 60%, values that appear reasonable based on recent work reported with this membrane type . It is also logical that the number of pores participating in the emulsification increases with the injection flow rate, as the transmembrane pressure will increase.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies were performed at constant pressure and showed that an increase in viscosity led to a decrease in transmembrane flux and to smaller oil droplets due to increase of wall shear stress inside the membrane pores. Also, in DME, only few studies reported the production of W/O emulsions, mainly micron size emulsions with kerosene as the continuous phase with different types of membranes or surface modifications [18,19,20] or with toluene [21]. A study reported the production of W/O emulsions suitable for cosmetics or dermatological applications with mineral oil as the continuous phase [22].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to use in ME, the SS membranes (both disc and tubular) and additional inner rod underwent a standard cleaning procedure. 26 Briefly, the items were immersed sequentially in an ultrasonic bath for 1 min in deionized water, 4 M NaOH, deionized water, 10 % wt citric acid, and finally deionized water. The items were soaked for 10 min in the acid and base solutions after sonication and were rinsed with tap water afterward, before being transferred to deionized water.…”
Section: Methodsmentioning
confidence: 99%